Voices from Maine Fishing Communities, a Selection of Oral History Interviews - Springuel, Natalie (Maine Policy Review, 2023)
Maine’s commercial fisheries have long been considered a backbone of the state’s coastal economy and culture. Mainers are proud of that fisheries heritage, sharing stories around the kitchen table and on the docks for generations. Since the 1970’s and earlier, ever-evolving technology has allowed us to record some of these stories for posterity. Oral history interview tapes are hidden away in dozens of archives, libraries, historical societies, institutions, and attics throughout Maine and beyond. It is our hope that the snippets presented here will open a window into the lives of people who live and have lived in Maine’s fishing communities and make their living on the ocean.
Keywords: commercial fisheries; oral history